2022
DOI: 10.3390/chemosensors10070257
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Citric Acid from Citrus Peels: Ultrasound-Assisted Extraction Optimized by Response Surface Methodology

Abstract: The production of citrus juice generates a large quantity of by-products, which are often discarded or used for animal feed. However, several studies have shown its richness in valuable compounds, namely organic acids. Thus, this work intended to valorize orange and lime peels as renewable sources of citric acid. An experimental design combining five levels of the independent variables time (2–45 min), ultrasonic power (50–500 W), and ethanol proportion (0–100%) was implemented and response surface methodology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 35 publications
0
5
0
1
Order By: Relevance
“…While all OP and PDB systems showed a relatively similar decreasing trend of pH, the initial pH value was found to be lower in the OP medium (5.50) than that in the PDB medium (5.80). Acidity was introduced with OP, since it is reported that OP contains organic acids such as citric acid (Fernandes et al ., 2022). In contrast, the pH value was higher (4.55) in OP than that (4.48) in PDB at the end of fermentation, which is reasonable considering that A. niger directly used the glucose in the PDB for acid production.…”
Section: Resultsmentioning
confidence: 99%
“…While all OP and PDB systems showed a relatively similar decreasing trend of pH, the initial pH value was found to be lower in the OP medium (5.50) than that in the PDB medium (5.80). Acidity was introduced with OP, since it is reported that OP contains organic acids such as citric acid (Fernandes et al ., 2022). In contrast, the pH value was higher (4.55) in OP than that (4.48) in PDB at the end of fermentation, which is reasonable considering that A. niger directly used the glucose in the PDB for acid production.…”
Section: Resultsmentioning
confidence: 99%
“…Proteins represent one of the most concentrated nutrients in legumes, and they can be easily used as components in innovative human foods. In addition, legumes have higher protein content than cereals: therefore, they represent a primary source of amino acids for humans [17].…”
Section: Discussionmentioning
confidence: 99%
“…Sehingga semakin banyak ekstrak yang ditambahkan maka konsentrasi asam sitrat yang juga meningkat dan membuat nilai pH semakin menurun. Hal ini sejalan juga dengan penelitian yang dilakukan oleh Fernandes et al (2022), bahwa asam sitrat yang ditambahkan saat ekstraksi dapat membuat suasana asam pada hasil ekstraksi karena asam sitrat yang bersifat asam, sehingga semakin banyak asam sitrat yang ditambahkan maka pH produk yang dihasilkan akan semakin asam.…”
Section: Phunclassified